2018
DOI: 10.1016/j.jjcc.2017.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Different indicators for postprocedural mitral stenosis caused by single- or multiple-clip implantation after percutaneous mitral valve repair

Abstract: 3D TEE derived MVOA predicts the postprocedural MS after 1-clip implantation, however, preprocedural ML diameter of LV inflow orifice is more useful to predict after 2-clip implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 29 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…Itabashi et al 23 showed that increased LV and MV dimensions might be accountable for a somewhat lower intraprocedural MG in a comparable cohort after one‐clip implantation. Contrary to our findings, patients with FMR showed a tendency for developing higher intraprocedural MG in this study, which might be due to smaller annular dimensions in their study cohort (AP diameter: 32 vs 38 mm).…”
Section: Discussionmentioning
confidence: 98%
“…Itabashi et al 23 showed that increased LV and MV dimensions might be accountable for a somewhat lower intraprocedural MG in a comparable cohort after one‐clip implantation. Contrary to our findings, patients with FMR showed a tendency for developing higher intraprocedural MG in this study, which might be due to smaller annular dimensions in their study cohort (AP diameter: 32 vs 38 mm).…”
Section: Discussionmentioning
confidence: 98%
“…Two predictors of a MV mean PG ≤ 4 mmHg after clip deployment in PMR were preprocedural mitral valve opening area of (MVOA) ≥ 3.94 cm² and medial-lateral diameter of left ventricle (LV) inflow orifice ≥ 3.23 cm for patients receiving one implanted clip. In case of two clips, cut-offs were 4.82 cm² and 3.29 cm, respectively [38] .…”
Section: Pmr Only Collectivementioning
confidence: 99%
“…Comparable to PMR, preprocedural MVOA and medial-lateral diameter of LV inflow orifice can also predict postprocedural mitral stenosis. For one and two clips, the cut-off values were 3.77 cm²/5.05 cm² and 3.03 cm/3.39 cm, respectively [38] .…”
Section: Smr Only Collectivementioning
confidence: 99%
“…[8][9][10][11] Occasionally, the chance of producing a relevant MS following the implantation of 2 or more clips is not negligible. Patients expected to develop this complication can be identified in advance by echocardiography on the basis of the initial valve area 12 and the intercommissural jet extension/location. In these patients, the target should be maximal reduction of MR and minimal increase of gradient across the valve.…”
mentioning
confidence: 99%